CONTRIBUTING FACTORS TO THE TURNOVER INTENTION OF MEDICAL EMPLOYEES OF NATIONAL HEART INSTITUTE KUALA LUMPUR (IJN) - Mohd Yunus, Jasmani; Mahajar, Abdul Jumaat (International Business Education Journal, 2014)
The purpose of this paper is to present the findings on whether job satisfaction which is pay, promotion, the job itself supervision, demographical factors which age and tenure, have any relationship with turnover intention among medical employees of National Heart institute Kuala Lumpur (IJN). Quantitative data were collected via a questionnaire distributed amongst the medical employees of IJN. A total of 210 medical employees of IJN completed the questionnaire. Respondents were selected through systematic sampling as the sample of study. The result shows that pay, supervision, promotion, and the job itself were significantly related to turnover intention while the demographical factors namely age and tenure were not significantly related. The research also found that the most dominant factor influencing the turnover intention among IJN’s medical employees was pay.